Measuring charged particle multiplicity with early ATLAS public data - Ustun, G.; Barut, E.; Bektas, E.; Ozcan, V. E. (IOP PUBLISHING LTD, 2017)
We study 100 images of early LHC collisions that were recorded by the ATLAS experiment and made public for outreach purposes, and extract the charged particle multiplicity as a function of momentum for proton-proton collisions at a centre-of-mass energy of 7 TeV. As these collisions have already been pre-processed by the ATLAS Collaboration, the particle tracks are visible, but are available to the public only in the form of low-resolution bitmaps. We describe two separate image processing methods, one based on the industry-standard OpenCV library and C++, another based on self-developed algorithms in Python. We present our analysis of the transverse momentum and azimuthal angle distributions of the particles, in agreement with the literature.
Keywords: Large Hadron Collider; particle tracking; image processing; charged particle multiplicity; Education & Educational Research; Physics